8086 Microprocessor. - Das, Layla b. (2010)
The book is designed for an undergraduate course on 16-bit microprocessor and Pentium. The text comprehensively covers both the hardware and software aspects of the subject with equal emphasis on architecture, programming and interfacing.
17.1 The Modern PC -- 17.2 The Mother Board -- 17.3 Chipset -- 17.4 Transfer Speed -- 17.5 Expansion Buses -- 17.6 ATA -- 17.7 Memory - SIMM and DIMM -- 17.8 System BIOS -- 17.9 New Motherboards -- 17.10 Other I/O Devices -- 17.11 PS/2 -- 17.12 Form Factors -- 17.13 Laptops -- Key Points of this Chapter -- Questions -- Exercise -- Appendix A -- Appendix B -- Appendix C -- Appendix D -- Appendix E -- Bibliography -- Index.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2018. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books